BOXING AS AN ALTERNATIVE TO PHYSICAL EDUCATION CLASSES FOR UNIVERSITY STUDENTS (Physical Culture and Sport: Scientific Perspective, 2025)
This article provides an in-depth theoretical substantiation of the feasibility of introducing boxing as an alternative form of physical education classes for university students in non-specialized higher education institutions. The relevance of the study is determined by current trends in higher education, including increased academic workload, reduced levels of students’ motor activity, sedentary lifestyles, and a steady decline in physical and functional health indicators among student youth. Under such conditions, traditional physical education programs often fail to ensure adequate motivation, systematic participation, and sustainable health-enhancing effects.Boxing is considered in the article as a versatile and multifunctional means of physical education that combines the development of physical fitness, psychophysiological functions, and moral-volitional qualities. The study synthesizes contemporary scientific findings related to students’ physical fitness levels, motivation for physical activity, and the effectiveness of sports-oriented models of physical education. Particular emphasis is placed on the advantages of a sports-oriented approach based on voluntary choice of physical activity, which significantly increases intrinsic motivation and students’ engagement in the educational process.The analysis of existing educational and author-designed boxing programs revealed both their strengths and limitations when applied in the context of higher education institutions. It is noted that many programs are adapted from youth sports schools and are overly focused on competitive outcomes, which may limit their accessibility for beginners and female students. Therefore, the article substantiates the necessity of modifying boxing-based physical education programs toward a health-oriented, educational, and recreational focus.Special attention is given to a gender-sensitive approach to organizing boxing classes. The importance of considering physiological characteristics of the female body, including the phases of the menstrual cycle, is emphasized as a prerequisite for ensuring safety, effectiveness, and positive health outcomes. The study highlights the effectiveness of game-based and controlled-contact teaching methods, which reduce injury risk, enhance emotional involvement, and create a positive motivational climate during classes.The findings confirm that the rational use of boxing elements in physical education classes contributes to the comprehensive development of students’ physical qualities, improvement of functional capacities, formation of self-discipline, self-control, and a stable motivation for a healthy lifestyle. The results of the theoretical analysis may serve as a methodological basis for the development of modern boxing-oriented physical education programs for students of various specialties and levels of physical preparedness.
Keywords: physical education; university students; boxing; sports-oriented training; motivation; gender-sensitive approach